A review: Material and structural properties of UHPC at elevated temperatures or fire conditions. (October 2021) - Zhu, Yanping; Hussein, Husam; Kumar, Aditya; Chen, Genda
Abstract: Ultra-high-performance concrete (UHPC) shows high tensile strength, compressive strength, and durability compared to normal strength concrete (NSC). However, high compactness, low permeability, and absence of capillary pores might reduce the spalling resistance of UHPC under elevated temperatures and fire conditions compared to NSC and high strength concrete (HSC). There are limited studies on the UHPC at elevated temperatures and fire loading in both material and structural applications. Basic understanding stems from the extension of NSC and HSC under elevated temperatures, although some debates still exist among different mechanisms. As UHPC has various constituents and high strengths, the mechanisms for NSC and HSC might not be suitable for understanding the complicated behavior of UHPC at elevated temperatures with spalling behavior. Also, the UHPC fire resistance improvement is needed as more applications use UHPC in new and existing structures. Therefore, this study reviews the recent advancements in the behavior of UHPC under elevated temperatures and provides new emerging insights on the UHPC mechanism of fire performance. Some strategies for enhancing the high-temperature performance of UHPC are suggested based on the existing understandings.